Multiplatform system oriented to telemedicine - Elizabeth Arelli Liñan Espinoza; Erich Jordy Echevarría Carpio; Laberiano Andrade-Arenas (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
The research arises from the need that was seen in people in recent years due to COVID-19, since remote medical care was required to avoid contagion, that it was developed with the Flutter tool and it is oriented towards telemedicine, which provides a medical evaluation service between patients and doctors. For the development of the methodology, the agile methodology of extreme programming "XP" was implemented, since it is of great help for the development of the system, the proto-types, and their different phases, since, compared to other methodologies, XP was the that gave more results in less time, which allowed us to have a faster development. The objective of the research is to implement a multiplatform system oriented to expert telemedicine. It has been possible to develop a basic demonstration of the system that would be the video calls, one of the most important functions of the entire system, and its operation has been effective as has been demonstrated in the results of this project, in which it was carried out carried out a survey of 50 questions and 95% agreed with the multiplatform system, since it would be of great help for several people.